Participation as a medium for economic empowerment among microfinance scheme beneficiaries in Kano, Nigeria - Saidu, Mohammed Bashir; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Ahmad, Nobaya (IDOSI Publications, 2014)
Participation is a vital component in community development projects such as microfinance scheme. The aim of microfinance is the provision of micro-financial services to economically-active-poor and low income households to enable them engage in income generating activities. This initiative could only be achieved through people participation in the scheme. This study examined the change in income among farmers beneficiaries of microfinance scheme in Kano. Data was collected from 364 respondents using structured questionnaire from six local government areas of Kano state. Paired sample t-test shows significant difference between income before(M=122,058.242,SD=116,312.049) and income after ( M= N175,137.088,SD= N72,611.637) participating in microfinance scheme (t= -14.803, p< .05, effect size = .613). Based on this(363)analysis the authors concluded that beneficiaries of microfinance scheme in Kano were economically empowered. The authors recommended that participating in microfinance scheme is an appropriate strategy to achieve economic empowerment.